Post War Justice: Jus Post Bellum for Just War and Peace - Rathour, Mansi (ETHICS IN PROGRESS, 2023)
This paper aims to address a key topic of speculation within political philosophy, namely the Just War Theory. The Just War Theory works to ethically restrain wars based on principles listed out in jus ad bellum (reasons to go to war) and jus in bello (conduct during war). As such, the theory dominated by the debate between the ‘traditionalists’ and ‘revisionists’ who are concerned about the integration of jus post bellum as the third branch of just war theory and feel it is better suited to the domain of international politics and security. This paper explores this lacunae over the neglect of jus post bellum (post war justice) within the just war discourse. By identifying the limitations of a minimalist jus post bellum and this misrepresentation of peace with security, this paper defends a maximalist account of jus post bellum and also situates post war justice as a necessary third branch of the Just War Theory. The challenges to taking such an extensive stance on post war justice are also addressed. As the first two branches of just war theory have been codified, the neglect of the post war stage leads to unrestrained war endings and ad-hoc solutions. Any just war theory needs to recognize the legitimacy of the third branch of post war justice as well, as only then can the Just War Theory function to restrain wars.